Simhadri super thermal power project (A) - Pandey, Ajay; Morris, Sebastian (London : Indian Institute of Management, Ahmedabad, 2006)
The case is about the coal-based Simhadri Thermal Power Project executed by the National Thermal Power Corporation NTPC in the late 90s. The case provides a setting for discussing the issues related to the Indian electricity sector and analysing the likely impact of the independent power producer (IPP) policy, which allowed foreign companies to invest in electricity generation in India and attempted reforms in the sector such as reduction of tariffs.The introduction of foreign and private companies into the Indian energy sector proved to be a major problem for the NTPC, in eroding their dominance in the generation of electricity.
Originally published in Pandey, A., & Morris, S. (2006). Simhadri Super Thermal Power Project (A). ECO0350(A). Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; National Thermal Power Corporation (India); Electric utilities -- India -- Management -- Case studies